A Prospective Cohort Study of Death Related to Opioid Use in Older Patients with a Diagnosis of Cancer (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: analgesics; opioid; fatal outcome; neoplasms; geriatric assessment